Effectiveness of an Activator in Early Treatment of a Class II Retrognathic Mandible : A Case Report - Withayanukonkij, Wisama (Thai Journal of Orthodontics, 2023)
This case report showed a 13 years old Thai boy with a chief complaint of having proclined teeth and spacing around his upper incisors. The main problem was a large overjet due to upper incisor proclination in combination with anterio-posterior skeletal discrepancies by a retruded position of the mandible. The treatment plan included two phases; the first phase was growth modification of the mandible with pre-pubertal growth spurt potential, and the second phase was conventional orthodontic treatment to correct the residual dental problem. The initial treatment was an arch expansion with an upper lateral expansion plate to coordinate the upper and lower arch for four months and to guide the mandible growth with an activator appliance by wearing it at least 12 hours/day for seven months. Progression was evaluated at the end of the first phase. The second phase period was a fixed appliance for twenty months. After treatment, the results showed a satisfactory lateral profile and alignment of teeth where the upper incisor position was corrected and a normal position of the mandible was presented. These outcomes suggest that growth modification works for severe Class II skeletal discrepancies, especially in young patients with future growing potential, as it decreases the severity and enhances normal skeletal growth pattern that decrease the chance of orthognathic surgery.